Integrating STEM into the Formal and Instructional Curriculum to Support Machine Construction Design - Sudjimat, Dwi Agus; Romlie, Maftuchin Romlie; Sudjono, Imam Sudjono; Subandi, Mahfudi Sahly (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
The design of machine construction is one of the subjects that often becomes a stumbling block for students of the Mechanical Engineering Education Study Program to graduate on time. Many factors cause it, including the weakness of students using STEM content in designing machine construction and the lack of contextual learning strategies for STEM-loaded courses with machine construction design tasks. This qualitative study aims to (1) identify the STEM content of the Scientific and Expertise Subject group, (2) describe the pattern of integrating STEM content in the formal and instructional curriculum, and (3) describe the learning pattern of the STEM content course. Research data were collected through document analysis, semi-open questionnaires, and FGD. The results showed (1) identified 15 scientific and skill courses containing STEM content that supported the work on machine construction design tasks, (2) integration of STEM-loaded courses in the formal curriculum was carried out by structuring their presentation before or at the same time as the presentation of the Mechanical Construction Design Course, being in the instructional curriculum is carried out by integrating learning experiences related to the design of machine construction in Lecture Event Unit, and (3) the learning pattern of courses containing STEM content should be carried out using a problem-based learning model where the problems are directly related to and or taken from machine construction design tasks.